Penyuluhan Hukum Tentang Batas Usia Minimal Perkawinan Berdasarkan UU No. 16 Tahun 2019 Tentang Perubahan Atas UU No.1 Tahun 1974 Tentang Perkawinan Di Lingkungan Anggota PKK Merjosari - Hery Setiawan; Gasper Doroh; Ferdinan Pakage; Darmawati Darmawati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This study aims to understand the understanding and attitude of PKK members in the Merjosari environment to the minimum age limit of marriage stipulated in law no. 16 of 2019 on amendments to law No. 1 of 1974 on marriage, and to explore the impact of legal counseling in raising public awareness of the issue of early marriage. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, Focus Group Discussion (FGD), and participatory observation. Informants of this study were members of PKK Merjosari who were selected by purposive sampling. The results showed that most PKK members were already aware of changes in the minimum age for marriage, but their understanding of the long-term impact of early marriage on health, education, and social welfare was still limited. Attitudes toward early marriage tend to favor such changes, arguing that early marriage risks hindering education and health. The legal counseling provided received a positive response, although some members still felt that the information provided was less in-depth and more theoretical. Legal counseling is proven to affect the change in attitudes of PKK members, who are now more aware of the importance of regulating the minimum age of marriage for the protection of women and children.